Improving the economic and humanistic outcomes for diabetic patients: making a case for employer-sponsored medication therapy management - Pinto SL; Kumar J; Partha G; Bechtol RA (Dove Medical Press, 2013)
Sharrel L Pinto, Jinender Kumar, Gautam Partha, Robert A BechtolThe Pharmaceutical Care and Outcomes Research Laboratory, Department of Pharmacy Practice, College of Pharmacy and Pharmaceutical Sciences, The University of Toledo, Toledo, OH, USABackground: The purpose of this study was to determine the cost savings of a pharmacist-led, employer-sponsored medication therapy management (MTM) program for diabetic patients and to assess for any changes in patient satisfaction and self-reported medication adherence for enrollees.Methods: Participants in this study were enrollees of an employer-sponsored MTM program. They were included if their primary medical insurance and prescription coverage was from the City of Toledo, they had a diagnosis of type 2 diabetes, and whether or not they had been on medication or had been given a new prescription for diabetes treatment. The data were analyzed on a prospective, pre-post longitudinal basis, and tracked for one year following enrollment. Outcomes included economic costs, patient satisfaction, and self-reported patient adherence. Descriptive statistics were used to characterize the population, calculate the number of visits, and determine the mean costs for each visit. Friedman’s test was used to determine changes in outcomes due to the nonparametric nature of the data.Results: The mean number of visits to a physician’s office decreased from 10.22 to 7.07. The mean cost of these visits for patients increased from $47.70 to $66.41, but use of the emergency room and inpatient visits decreased by at least 50%. Employer spending on emergency room visits decreased by $24,214.17 and inpatient visit costs decreased by $166,610.84. Office visit spending increased by $11,776.41. A total cost savings of $179,047.80 was realized by the employer at the end of the program. Significant improvements in patient satisfaction and adherence were observed.Conclusion: Pharmacist interventions provided through the employer-sponsored MTM program led to substantial cost savings to the employer with improved patient satisfaction and adherence on the part of employees at the conclusion of the program.Keywords: costs, patient satisfaction, adherence, pharmaceutical care, diabetes